2020
DOI: 10.1016/j.psychres.2020.113390
|View full text |Cite
|
Sign up to set email alerts
|

Trends in suicidal ideation over the first three months of COVID-19 lockdowns

Abstract: To reduce viral spread during the first months of the COVID-19 pandemic, most communities across the U.S. engaged in some form of stay-at-home restrictions or lockdowns that limited social interaction and movement outside the home. To determine the effect of these restrictions on suicidal ideation, a total of 3,120 individuals completed the Patient Health Questionnaire (PHQ-9) at one of three time points from April through June 2020. The percentage of respondents endorsing suicidal ideation was greater with ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 5 publications
7
80
2
7
Order By: Relevance
“…For some types of research, MTurk samples have been found to be more representative of attitudes than nationally representative panels [ 30 ]. During the course of the COVID-19 pandemic, we have collected data from multiple similar sized samples in the past that have all provided reliable data that are closely matched with other recent findings about psychological and behavioral health status [ 31 , 32 , 33 , 34 , 35 , 36 ]. For political ideology, as assessed here, data from MTurk surveys have been shown to be highly reliable and consistent with nationally representative samples [ 37 ].…”
Section: Discussionmentioning
confidence: 75%
“…For some types of research, MTurk samples have been found to be more representative of attitudes than nationally representative panels [ 30 ]. During the course of the COVID-19 pandemic, we have collected data from multiple similar sized samples in the past that have all provided reliable data that are closely matched with other recent findings about psychological and behavioral health status [ 31 , 32 , 33 , 34 , 35 , 36 ]. For political ideology, as assessed here, data from MTurk surveys have been shown to be highly reliable and consistent with nationally representative samples [ 37 ].…”
Section: Discussionmentioning
confidence: 75%
“…Risk factors identified for thoughts of suicide or self-harm in the general population were young age (Czeisler et al, 2020;Fitzpatrick et al, 2020;Li et al, 2020), ethnic minority background (Czeisler et al, 2020;Fitzpatrick et al, 2020), essential worker status (Czeisler et al, 2020), families with children (Fitzpatrick et al, 2020), being unmarried (Fitzpatrick et al, 2020), prior psychiatric disorder (Hao et al, 2020), poorer physical health (Li et al, 2020), current lockdown (Gratz et al, 2020;Killgore et al, 2020a), less social support (Li et al, 2020), lower psychological resilience (Killgore et al, 2020e), concern about COVID-19 (Ahorsu et al, 2020;Islam et al, 2020;Killgore et al, 2020c;Wu et al, 2020b), lower adherence to infection control guidance (Li et al, 2020), loneliness and (Killgore et al, 2020b(Killgore et al, , 2020d insomnia (Killgore et al, 2020c). There was no evidence for the difference in the prevalence of thoughts of suicide when comparing hospital staff to the general population (Zhou et al, 2020), or when comparing frontline v. non-frontline health care staff (Cai et al, 2020).…”
Section: Thoughts Of Suicide or Self-harmmentioning
confidence: 99%
“…Studies conducted during the present Covid-19 pandemic confirmed these findings and showed increased rates of anxiety, depression and traumatic stress across the general population in various countries 2 . Some studies also showed increases in suicidal ideation 3, 4 , notably in conditions of lockdown 5 . In France, a regular web-based survey of a representative sample of the general population conducted by Santé Publique France (“Public Heath France”) since March 16th, 2020 (https://www.santepubliquefrance.fr/etudes-et-enquetes/covid-19-une-enquete-pour-suivre-l-evolution-des-comportements-et-de-la-sante-mentale-pendant-l-epidemie) showed an initial increase in depression and anxiety levels associated with sleep problems and alcohol and tobacco use, followed by a relative improvement of these indexes after the end of the lockdown.…”
Section: Introductionmentioning
confidence: 97%